Rixen, Thomas; Lora Anne Viola; Michael Zürn. Historical Institutionalism and International Relations. Explaining Institutional Development in World Politics. Oxford: Oxford University Press. 2016. 229 p. (2017)
Este documento contiene en texto completo el articulo Rixen, Thomas; Lora Anne Viola; Michael Zürn. Historical Institutionalism and International Relations. Explaining Institutional Development in World Politics. Oxford: Oxford University Press. 2016. 229 p. publicado en Desafíos; Vol. 30, Núm. 1 (2018): (enero-junio) Procesos de regionalización: nuevas y antiguas perspectivas; 389-392;2145-5112;0124-4035;10.12804/revistas.urosario.edu.co/desafios/30-1.2018